Terrorism as an external threat factor in global value chains. (30th December 2019) - Bader, Benjamin; Suder, Gabriele; Grosse, Robert
Abstract: Global terrorism incidents and business‐related threats have intensified in scale and scope over the past 17 years. Multinational corporations are thus exposed to direct and indirect negative impacts on their international activities. Previous research lacks thorough theoretical frameworks to analyze these impacts. The global value chain (GVC) framework offers a perspective that is both comprehensive and quantifiable for the evaluation and expansion of this prior research. The GVC enables us to assess terrorism impacts on international business overall and at each stage of the value chain. On this basis, we develop a "terrorism resilience theory") that can be used in future theoretical and managerial analyses of the response to terrorism risk.